2011
DOI: 10.2188/jea.je20110003
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of the International Physical Activity Questionnaire (IPAQ) in Elderly Adults: The Fujiwara-kyo Study

Abstract: BackgroundThe International Physical Activity Questionnaire (IPAQ) is a self-reported questionnaire for assessing physical activity and has been tested in 12 countries among adults aged 18 to 65 years. The present study evaluated the reliability and validity of the IPAQ among adults aged 65 years and older.MethodsThe study included 164 men and 161 women selected from participants of the Fujiwara-kyo Study, a prospective cohort of elderly Japanese adults. To examine test–retest reliability, the participants wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
238
1
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(261 citation statements)
references
References 29 publications
5
238
1
7
Order By: Relevance
“…It could be hypothesized that a highly educated, young test population may also increase the test-retest reliability of the instrument. Another recent study 39 that solely sampled elderly subjects showed ICCs for the short form of the IPAQ that were comparable to those of the present study, with ICCs for total activity scores ranging from 0.50 to 0.65. The Short Questionnaire to Assess Health-enhancing physical activity, a physical activity questionnaire closely related to the IPAQ, found test-retest reliability comparable to that of the present study.…”
Section: Discussion Ssupporting
confidence: 86%
See 1 more Smart Citation
“…It could be hypothesized that a highly educated, young test population may also increase the test-retest reliability of the instrument. Another recent study 39 that solely sampled elderly subjects showed ICCs for the short form of the IPAQ that were comparable to those of the present study, with ICCs for total activity scores ranging from 0.50 to 0.65. The Short Questionnaire to Assess Health-enhancing physical activity, a physical activity questionnaire closely related to the IPAQ, found test-retest reliability comparable to that of the present study.…”
Section: Discussion Ssupporting
confidence: 86%
“…A previous study pointed out that the level of reliability is linked to the test-retest interval used. 39 Reliability was higher when a short time interval was used (8 days or less), whereas a longer interval (2-3 weeks) accounted for a lower reliability. With this in mind, van Poppel et al, 41 as they pointed out themselves, might have overestimated reliability scores due to a 3-day measurement interval.…”
Section: Discussion Smentioning
confidence: 90%
“…The correlation coefficient between the IPAQ-S total MET min/week and the average dayactivity counts was above 0.5, which has been considered as adequate construct validity by van Poppel at al. 148 and was in line with that found by Tomioka et al 149 in elderly men and women.…”
Section: Physical Activitysupporting
confidence: 91%
“…However, respondents were usually diagnosed by subjective methods (questionnaires) [9,10,11]. It has been proved many times that the accuracy of questionnaire research among seniors decreases with age [12,13]. It is therefore necessary to intensify research on the effects of physical activity of the elderly by using objective measurement methods.…”
Section: Introductionmentioning
confidence: 99%